How Do International Economic Laws Impact Sustainable Development Goals? - Sabirin, Ahmad; Zuhra, Amalia (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
IEL plays an important role in achieving the SDGs which is influenced by the design and application of the law. International trade agreements can limit government policies that support sustainable development, while international financial regulations affect the flow of funds for sustainable projects. The role of multilateral development banks and international investment is significant in supporting the SDGs. This study examines the extent to which IEL affects the implementation of the SDGs and recommends best practices and strategies that can be adopted to increase IEL's contribution to sustainable development. This research uses a qualitative approach and analyzes legal documents, case studies, and expert interviews. The interesting findings of this study show that the IEL supports the rule of law by promoting transparency and accountability. However, there are still challenges such as power imbalances between developed and developing countries, legal compliance, and the integration of IELs with the SDGs. In addition, IELs can support or hinder the SDGs, depending on their design and implementation. The impact of free trade agreements on the SDGs shows the economic and environmental benefits as well as the challenges of inequality and environmental degradation. Meanwhile, the recommendations that can be given from this study are that to increase IEL's contribution to the SDGs include the integration of sustainable policies in trade agreements, green investment, strengthening law enforcement mechanisms, transparency and stakeholder participation, and the development of international cooperation.